THE EFFECT OF CAPITAL STRUCTURE ON FIRM VALUE WITH PROFITABILITY AS A MODERATING VARIABLE (Case Study of Consumer Non-Cyclical Sector Companies Listed on the Indonesia Stock Exchange for the 2021–2024 Period) - Fauzia Naningsi Ibrahim; Hais Dama; Idham Masri Ishak (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
This study aims to analyze the effect of capital structure on firm value with profitability as a moderating variable in consumer non-cyclical sector companies listed on the Indonesia Stock Exchange during 2021–2024. Capital structure was measured using Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER), firm value was proxied by Price to Book Value (PBV), while profitability was measured using Return on Assets (ROA). This research applied a quantitative approach using secondary data obtained from annual financial reports. The sample consisted of 154 observations selected through purposive sampling. Data analysis was conducted using multiple linear regression and Moderated Regression Analysis (MRA) with SPSS software. The results show that DAR has a positive and significant effect on firm value, while DER has a negative but insignificant effect on firm value. Simultaneously, DAR and DER significantly affect firm value. Furthermore, profitability (ROA) is proven to strengthen the relationship between DAR and firm value as well as between DER and firm value. These findings indicate that an optimal capital structure supported by strong profitability can increase firm value. Therefore, companies should maintain a balanced financing composition and improve profitability to enhance market valuation.